Multi-Tissue Methylation Clocks for Age and Sex Estimation in the Common Bottlenose Dolphin - Todd R. Robeck; Zhe Fei; Amin Haghani; Joseph A. Zoller; Caesar Z. Li; Karen J. Steinman; Stacy Dirocco; Lydia Staggs; Todd Schmitt; Steve Osborn; Gisele Montano; Magdalena Rodriguez; et al. (Frontiers in Marine Science, 2021)
Accurate identification of individual ages within wild bottlenose dolphins ( Tursiops truncatus ) is critical for determining population health and the development of population management strategies. As such, we analyzed DNA methylation (DNAm) patterns by applying a custom methylation array (HorvathMammalMethyl40) to both blood ( n = 140) and skin samples ( n = 87) from known age or approximate age (0–57 years) bottlenose dolphins. We present three bottlenose dolphin specific age estimation clocks using combined blood and skin [48 CpGs, R = 0.93, median absolute error (MAE) = 2.13 years], blood only (64 CpGs, R = 0.97, error = 1.46 years) and skin only (39 CpGs, R = 0.95, error = 2.53). We characterized individual cytosines that correlate with sex and age in dolphins and developed a sex estimator based on 71 CpGs that predicts the sex of any odontocete species with 99.5% accuracy. The presented epigenetic clocks are expected to be useful for conservation efforts and for determining if anthropogenic events affect aging rates in wild populations.